2014
DOI: 10.1007/s12039-014-0720-y
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, structural investigation and kinetic studies of uranyl(VI) unsymmetrical Schiff base complexes

Abstract: Uranyl(VI) complexes with unsymmetrical N 2 O 2 Schiff base ligands were synthesized and characterized. Their characterization was performed using UV-Vis, 1 H NMR, cyclic voltammetry, single-crystal X-ray crystallography, IR, TG and C.H.N. techniques. X-ray crystallography of the complexes show that beside coordination of the tetradentate Schiff base, one DMF molecule is also coordinated. In order to investigate the effect of the substitutional groups of the Schiff base on the oxidation and reduction potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
2
7
0
Order By: Relevance
“…The results clarified that uranyl complexes show better anticancer activities than ligands when both cells are examined [54][55][56][57][58][59]. By comparison with the literature results [8][9][10][11][12] of the activity of uranyl complexes as anticancer agents for many different cell lines, it was found that the Schiff's base uranyl complexes that were prepared in this study have more effective IC50, which indicated less toxicity than previously reported results, which may be because this is the first study that investigated their effect against ovarian cancer and melanoma cell lines.…”
Section: Anticancer and Toxicological Studiessupporting
confidence: 54%
“…The results clarified that uranyl complexes show better anticancer activities than ligands when both cells are examined [54][55][56][57][58][59]. By comparison with the literature results [8][9][10][11][12] of the activity of uranyl complexes as anticancer agents for many different cell lines, it was found that the Schiff's base uranyl complexes that were prepared in this study have more effective IC50, which indicated less toxicity than previously reported results, which may be because this is the first study that investigated their effect against ovarian cancer and melanoma cell lines.…”
Section: Anticancer and Toxicological Studiessupporting
confidence: 54%
“…[11] In general, U=O, UÀ O(phenolate) and UÀ N(azomethine) bond lengths in 1-4 are within the ranges reported for (UO 2 ) 2 + complexes having similar coordinating atoms. [10][11][12]…”
Section: X-ray Molecular Structuresmentioning
confidence: 99%
“…The amino and phenolic groups on salophens have the function of providing electrons, and salophens are widely used to adsorb the transition metals and the main group metals, so uranyl‐salophens formed by the coordination of uranyl ion (UO 2 2+ ) with salophens have become a research hotspot . Recently, two new uranyl‐salophens were characterized where the uranyl ion formed a complex in a twisted planar configuration with a coordination number of four, and the tetra‐coordinated uranyl could still coordinate with other atoms or groups . Due to this particularity of the uranyl‐salophens, their derivatives are widely used in molecular recognition, non‐formation catalysis and enzyme construction .…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] Recently, two new uranyl-salophens were characterized where the uranyl ion formed a complex in a twisted planar configuration with a coordination number of four, and the tetracoordinated uranyl could still coordinate with other atoms or groups. [14][15][16][17][18] Due to this particularity of the uranyl-salophens, their derivatives are widely used in molecular recognition, non-formation catalysis and enzyme construction. [19][20][21] In asymmetric catalysis, Castelli et al explored the catalytic performance of asymmetric uranyl-salophen and reaction kinetics of complexes formed by small molecules, finding that the unilateral substituents accompanying the uranyl-salophen derivatives continuously increased, and the association constant between uranyl-salophens and small molecules would gradually increase, which meant that catalytic performances improved.…”
mentioning
confidence: 99%